FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN IBU HAMIL MENGKONSUMSI FE TABLET : SISTEMATIK REVIEW - Febriana Muchtar; Wa Ode Salma; La Ode Alifariki (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
This systematic review aims to describe what factors are related to the compliance of pregnant women in consuming Fe. To carry out this brief systematic review, related literature searches were carried out on several sources, primarily PubMed Medline and Google Scholar Journals. Then a search engine related to Fe Consumption is used to make the work more meaningful and intensive. Then, the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines are followed to carry out the work with care. Finally, the combined effect size was calculated using the review manager and the Compressive Meta-analysis software. A total of 9 studies from several developing countries were included in this study because they had fulfilled several adjusted requirements. In general, the factors related to the compliance of pregnant women in consuming Fe (iron) include place of residence, mother's education, husband's education, number of pregnancies, number of deliveries, knowledge of anemia, mother's occupation, husband's occupation, number of family members, early registration, household income, illness experienced, disease management, and first visit for antenatal care, perceived benefits, perceived barriers, and family support, husband's support, maternal age. The compliance of pregnant women obtained in studies that have been carried out in several countries in the world to consume Fe supplementation is lower than the recommendations of the world health organization. Therefore, healthcare professionals should focus on increasing adherence to Fe supplementation by providing the recommended number of ANC visits.